Optimalizace renderování rozsáhlého terénu - Luner, Radek (Vysoké učení technické v Brně. Fakulta informačních technologií, 2010)
Práce se zabýva optimalizací renderování rozsáhlých terénů. Vysvětluje základní metody a datové struktury určené pro optimalizace. Popisuje principy metod ROAM, Geometrical clipmaps, GPU Based Geometrical Clipmaps, GeoMipMapping a Chunked LOD. Jsou zde popsány implementační detaily systému pro optimalizaci scény založeném na metodě GeoMipMapping.

This work is focusing on optimization of large scale terrain rendering. It explains basic methods and data structures for optimization. It describes fundamentals of methods such as ROAM, Geometrical clipmaps, GPU Based Geometrical Clipmaps, GeoMipMapping and Chunked LOD. It explains implementation details of system for terrain optimization based on GeoMipMapping method.
Optimization of Large Scale Terrain Rendering
Keywords: Optimalizace; terén; level of detail; frustum culling; ROAM; Goemetrical Clipmaps; GPU Based Geometry Clipmaps; GeoMipMapping; Chunked LOD; Optimization; terrain; level of detail; frustum culling; ROAM; Goemetrical Clipmaps; GPU Based Geometry Clipmaps; GeoMipMapping; Chunked LOD